Components of Reading Ability: Multivariate Evidence for a Convergent Skills Model of Reading Development - Vellutino, Frank R.; Tunmer, William E.; Jaccard, James J.; Chen, RuSan (Scientific studies of reading, 2007)
Elementary and middle school children were given a large battery of tests evaluating reading subskills and reading-related cognitive abilities. These measures were used to define latent representing skills and abilities believed to be important components of reading comprehension. Hypothesized relationships among these constructs were specified within the context of a structural model we call the "Convergent Skills Model of Reading Development," and developmental differences in the relative contribution made by each construct to reading comprehension performance were assessed through confirmatory factor analysis using the LISREL and AMOS programs. Results provide qualified support for the model and were interpreted as consistent with the major premises of both Gough and Tunmer's (1986) "Simple View" and Sticht's (1979) "Audread" models of reading.